2014
DOI: 10.1007/s11046-014-9779-8
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Transcriptional Response to Hypoxia in Aspergillus fumigatus Observed Using RNAseq Identifies a Novel Hypoxia Regulated ncRNA

Abstract: We utilized RNAseq analysis of the Aspergillus fumigatus response to early hypoxic condition exposure. The results show that more than 89% of the A. fumigatus genome is expressed under normoxic and hypoxic conditions. Replicate samples were highly reproducible; however, comparisons between normoxia and hypoxia revealed that greater than 23% and 35% of genes were differentially expressed after 30 and 120 minutes of hypoxia exposure, respectively. Consistent with our previous report detailing transcriptomic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Experimental evidence suggested that AFUB_099650 mRNA increased dramatically when exposed to hypoxia when using nitrate as its sole nitrogen source (Losada et al, 2014;Schinko et al, 2010;Zhou et al, 2009). pflavA-erg25A : : DsrbA was verified to have a single insertion by PCR and Southern blot analysis (Fig.…”
Section: Smo Genes Responsive To Hypoxiamentioning
confidence: 97%
“…Experimental evidence suggested that AFUB_099650 mRNA increased dramatically when exposed to hypoxia when using nitrate as its sole nitrogen source (Losada et al, 2014;Schinko et al, 2010;Zhou et al, 2009). pflavA-erg25A : : DsrbA was verified to have a single insertion by PCR and Southern blot analysis (Fig.…”
Section: Smo Genes Responsive To Hypoxiamentioning
confidence: 97%
“…At present, genome-wide transcriptional profiling data of the hypoxic stress response are available from several filamentous ascomycetes: A. nidulans, A. oryzae, A. fumigatus, and Trichoderma reesei (Barker et al 2012;Bonaccorsi et al 2006;Hillmann et al 2014;Kroll et al 2014;Losada et al 2014;Masuo et al 2010;Terabayashi et al 2012). A somewhat smaller number of studies have been published on proteomic changes of A. nidulans and A. fumigatus during adaptation to low oxygen partial pressures (Barker et al 2012;Shimizu et al 2009;Vödisch et al 2011).…”
Section: Gene and Protein Expression During Hypoxiamentioning
confidence: 99%
“…Later this proteomic study was complemented by a microarray experiment, which revealed in addition an altered cell wall, polysaccharide metabolism (many induced glucanases) and an increased metal ion transport (mitochondrial transporter, copper transport) upon hypoxia . Three further transcriptome/proteome surveys studied the batch growth of A. fumigatus at low O 2 levels in an oxygen-controlled fermenter (Barker et al 2012;Hillmann et al 2014;Losada et al 2014). The exposure time to hypoxia varied between 1, 2, and 24 h. Altogether, the number and type of genes whose expression changed significantly in abundance during hypoxic growth differed appreciably between the three studies.…”
Section: Gene and Protein Expression During Hypoxiamentioning
confidence: 99%
“…During infection, A. fumigatus must also adapt to the oxygen-limited environment of host tissues [7]. Losada et al [8] report the results of a study to determine the genome-wide expression profile of A. fumigatus exposed to a hypoxic environment. Using RNA-seq technology, the authors expand previous microarray data on the hypoxia transcriptome and provide intriguing evidence for the existence of a novel hypoxia-regulated non-coding RNA [8].…”
Section: Fungal Stress Responsementioning
confidence: 99%
“…Losada et al [8] report the results of a study to determine the genome-wide expression profile of A. fumigatus exposed to a hypoxic environment. Using RNA-seq technology, the authors expand previous microarray data on the hypoxia transcriptome and provide intriguing evidence for the existence of a novel hypoxia-regulated non-coding RNA [8]. Another central mediator of eukaryotic stress responses is the calcium/calmodulin-activated protein phosphatase calcineurin, which controls a pathway that regulates drug tolerance, morphogenesis, and virulence in a variety of pathogenic fungi, including A. fumigatus [9].…”
Section: Fungal Stress Responsementioning
confidence: 99%